Phenomenological approach in determining responses of hospitalised children experiencing a garden - Said, Ismail; Abu Bakar, Mohd Sarofil (Fakulti Alam Bina, UTM, 2006)
This study presents and describes a phenomenological approach of an experiment conducted on 31 middle childhood paediatric patients experiencing a hospital garden. The approach is a measure to collect behavioural data of the patients by examining the situated actions of patients in the garden context. As such the approach views the patient-in-garden as the unit of analysis. As a context, the garden is a play space where an individual patient interacts through play with physical elements as well as transacts with peers and caregivers. His behavioural responses are his actions and words suggesting his perceptual judgments towards the garden as a context. This study conducts an affective procedure to elicit the perceptual judgments and movement of the patients in their situated actions. The procedure ensures cooperation from the children without disrupting their play or intimating their moods. The study measures patients’ increased cognitive, physical and social functioning as restorative outcomes.